Ageing, Work, Organizationand Health - Hélène David; Serge Volkoff; Esther Cloutier; Francis Derriennic (Perspectives Interdisciplinaires sur le Travail et la Santé)
The paper begins by identifying the trends in the main fields of workplace change, and briefly summarizes their impacts on the ageing workforce. Very little work has been done on the service and care sectors, which are currently undergoing expansion, and these sectors have therefore been selected as the main targets for reflection. The paper goes on to examine the main organizational choices from the standpoint of their capacity to leave room for employees of all ages. The main issues facing ageing staff include flexibility and task variety, time constraints, work schedules, the collective aspects of work, learning and vocational training, and job insecurity. These aspects of workplace organization are addressed from the standpoint of the issues they raise for an ageing workforce, their impacts on health, possible exclusion mechanisms, the related management methods and flexibility. However, the complexity of the issues raised and the shortage of data and analyses raise more questions than they answer. The paper therefore concludes with a set of questions that may help orient future work on the subject.